Warts - A Sycosis Manifestation (Homoeopathy for All, 2024)
Diseases which are transmitted from  Human to human or animal to human  are called miasmatic diseases. =  acquired diseases. By “miasm” Hahnemann means  an infectious principle, which, when  taken into the organism, may set  up a specific disease. According to  Hahnemann, there were not only  miasms of acute disease, like the  infectious principle of scarlatina,  for example, but also of chronic  diseases. Among the latter he  recognised three-syphilis, sycosis  and psora.
Keywords: Sycosis (Excess); miasm; three-syphilis; Chronic miasms